Troubleshooting Electric Motors (Paperback) - Mazur Glen A. (Amer Technical Pub, 2005)
The book is not too complicated. It could give better explainations but the book sets a basic knowledge of motors. It explains the different types of motors and their pros and cons. The book has few equations and with basic knowledge of physics and electricity they can be understood. Calculus is not used in the book.